2020
DOI: 10.1515/ijfe-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Application of three-phase partitioning to the purification and characterization of polyphenol oxidase from antioxidant rosemary (Rosmarinus officinalis L.)

Abstract: Polyphenol oxidase (PPO) has been purified from the rosemary plant (Rosmarinus officinalis L.) through three-phase partitioning (TPP) and has been biochemically characterized. The optimized TPP consisted of 50% (w/v) ammonium sulfate and equal volumes of crude extract and tert-butanol prepared at pH 6.5 and room temperature. Using this system, PPO was purified 14-fold, with 230% recovery of activity from the middle phase. The partitioned enzyme had a molecular mass of 53 kDa. The highest enzyme activity was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Three-phase partitioning (TPP) is a method of crude purification of target proteins, which involves adding a certain proportion of salt and organic solvents to the crude extraction solution to create clear layering of the mixed solution [47]. This method promotes the aggregation of some of the proteins in the precipitation layer between the organic and aqueous phases, the dissolution of low-molecular-weight pigments, membrane lipids, etc., in the organic layer, and the dissolution of sugars and some proteins in the water layer.…”
Section: Three-phase Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-phase partitioning (TPP) is a method of crude purification of target proteins, which involves adding a certain proportion of salt and organic solvents to the crude extraction solution to create clear layering of the mixed solution [47]. This method promotes the aggregation of some of the proteins in the precipitation layer between the organic and aqueous phases, the dissolution of low-molecular-weight pigments, membrane lipids, etc., in the organic layer, and the dissolution of sugars and some proteins in the water layer.…”
Section: Three-phase Partitioningmentioning
confidence: 99%
“…The activity yields of TPP to sPPO and mPPO were 73.8% and 79.8%, respectively. With its advantages of simple operation, wide applicability, and high activity yield, TPP has been widely used in the extraction of PPO from various plants, including Rosmarinus officinalis L. [47], Lepiota procera [48], and Trachystemon orientalis L. [38]. The PPO from Trachystemon orientalis L. was purified 3.59-fold with a 68.75% total recovery of activity using the TPP procedure twice in a row [38].…”
Section: Three-phase Partitioningmentioning
confidence: 99%
“…Niphadkar and Rathod (2015) and Alici and Arabaci (2016) have reported 70% and 69% activity recovery values of PPO corresponding to 6.3and 3.6-fold purifications, respectively. Yuzugullu Karakus et al (2020) and ( 2021) have reported 230% and 120% activity recoveries of PPO corresponding to 14-and 20-fold purifications, respectively. In this study, PPO was purified to a higher fold than potato and borage PPO enzymes.…”
Section: Optimization Of Ppo Extraction Conditionsmentioning
confidence: 99%
“…This means the enzyme is more stable in neutral and alkaline pH rather than acidic pH. (Kavrayan and Aydemir, 2001), pawpaw (Bello et al, 2011), grape (Kaya and Bağci, 2021), artichoke (Aydemir et al, 2003), and rosemary (Yuzugullu Karakus et al, 2020) showed that the PPO enzyme is more stable in the pH ranges of 6.0-7.0, 6.0-8.0, 7.0, 6.0-8.0, 6.0-9.0, respectively. These observations are similar to the findings of I. purpurea plant, which shows that the enzyme is stable between pH 6.0 and 9.0.…”
Section: Effect Of Reaction Ph On Ppo Activity and Stabilitymentioning
confidence: 99%
“…PPO enzyme was puri cated by different biochemical methods such as ion exchange chromatography by using diethyl aminoethyl-sepharose or diethyl aminoethyl-A50 sephadex, gel ltration chromatography by using sephadex G-150 [14][15][16][17], Sephacryl S-200 [18] and three-phase partitioning [19,20]. Among these puri cation methods, a nity puri cation methods have been widely used in the separation of various carrier proteins which are used in phosphorylation, methylation, acetylation and ubiquitination [21] and unlike these such conventional chromatography methods [14][15][16][17][18][19][20], a nity chromatography is the most preferred one to warrant a high isolation of any enzyme from its initial material by using a speci c ligand of an enzyme which is bounded covalently to a crosslinked support matrix. Separation of an enzyme from a solid matrix was generally accomplished by changing of ionic intensity such as pH or salt concentration [22].…”
Section: Introductionmentioning
confidence: 99%